2013
DOI: 10.1055/s-0033-1349124
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Face Classification of Cushing's Syndrome in Women - A Novel Screening Approach

Abstract: In this preliminary analysis we found a good classification accuracy of Cushing's syndrome by face classification software. Testing accuracy is comparable to that of currently employed screening tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 4 publications
0
32
0
Order By: Relevance
“…This chapter aims to provide a basic explanation of the image analysis and classification method as it was used by the authors of this review. It has been extensively described in previous publications from our group from 2011 and 2013 (4,5). The principles of image analysis and classification as described are comparable within the studies presented in this review.…”
Section: Basic Description Of the Facial Image Analysis And Classificmentioning
confidence: 60%
See 1 more Smart Citation
“…This chapter aims to provide a basic explanation of the image analysis and classification method as it was used by the authors of this review. It has been extensively described in previous publications from our group from 2011 and 2013 (4,5). The principles of image analysis and classification as described are comparable within the studies presented in this review.…”
Section: Basic Description Of the Facial Image Analysis And Classificmentioning
confidence: 60%
“…The authors of this review also applied the method to the detection of CS in a proof-of-concept study and published the results in 2013 (5). For this, the experiments were repeated in the original setup with a cohort of 20 female patients suffering from endogenous or iatrogenic CS and 40 age-and gender-matched control subjects.…”
Section: Application In Cs and Current Researchmentioning
confidence: 99%
“…One recent study showed that face classification software correctly classified nearly all patients (85%) and controls (95%) using facial photographs. Further prospective research in patients suspected of having Cushing’s syndrome is needed to validate this tool (12). …”
Section: Signs and Symptoms Of Cushing’s Syndromementioning
confidence: 99%
“…The methods described in previous sections are suitable to be applied in other conditions as well. For example, the use of facial imaging has also been applied to evaluate facial abnormalities, using facial features and classifiers to assess conditions such as acromegaly [180], [181] and Cushing's syndrome [181], [182] or craniofacial deformations associated with specific syndromes [13], [136].…”
Section: G Other Conditionsmentioning
confidence: 99%